LIPID-PHOSPHOLIPID DISORDERS IN PATIENTS WITH COMORBID OVER NONALCOHOLIC FATTY LIVER DISEASE AND OBESITY ON THE BACKGROUND OF PATHOLOGY BILIARY TRACT DEPENDING ON BODY WEIGHT - Filippova, A.Yu. (World of Medicine and Biology, 2016)
Objective - to study changes in lipid-phospholipid indicators depending on body mass index (BMI) in patients with comorbid over non-alcoholic fatty liver disease (NAFLD) in combination with obesity (OB) and the pathology of the biliary tract (BT). Materials and methods. The study involved 112 patients with NAFLD in conjunction with OB and BT pathology, who at the time of sonographic and morphological study of liver biopsy revealed signs of hepatic steatosis. Among the 31 patients were males and 81 females. The average age of patients – (52,2±1,1) years. The control group consisted of 20 healthy individuals. BMI is determined by the formula Quetelet. Depending on the degree of increase in BMI of all patients with nonalcoholic hepatic steatosis (n=60) and nonalcoholic steatohepatitis (n=52), and OB were divided into three groups: those with a BMI of 25-29,9 kg/m2 – overweight; BMI 30-34,9 kg/m2 – OB I degree; BMI 35-39,9 kg/m2 – OB II degree. Qualitative and quantitative composition of lipids and phospholipids was studied by tonkosharovoy chromatography. Results and discussion. The changes in the parameters of the spectrum of lipids and phospholipids of blood serum in patients with nonalcoholic hepatic steatosis and nonalcoholic steatohepatitis in combination with OB and pathology BT depending on BMI. A significant breach of phospholipids (PL) indicators, free cholesterol, triglycerides, cholesterol esters, which progressed with increasing body weight and were considered by us as an adverse factor in the development and progression of NAFLD in conjunction with the OB in the background pathology BT. The revealed changes of the PL spectrum of blood serum in patients from the nonalcoholic hepatic steatosis and nonalcoholic steatohepatitis group was significantly dependent on the increase in BMI and according to the data obtained were characterized by a pronounced imbalance of certain factions – a decrease in the content of phosphatidylcholine and sphingomyelin, and a significant increase in lizoform PL – lysophosphatidylcholine and phosphatidylethanolamine. According to the correlation analysis found that increasing BMI decreased the levels of phospholipids (rs=-0,402, р0,001 and rs=-0,338, р0,05), phosphatidylcholine (rs=-0,317, р0,05 and rs=-0,423, р0,01), sphingomyelin (rs=-0,111, р>0,05 and rs=-0,385, р0,01) and the significant increase of free cholesterol (rs=0,624, р0,001 and rs=0,639, р0,001), triglycerides (rs=0,352, р0,01 and rs=0,359, р0,01), cholesterol ester (rs=0,387, р0,01 and rs=0,294, р0,05), lysophosphatidylcholine (rs=0,405, р0,001 and rs=0,499, р0,001), phosphatidylethanolamine (rs=0,557, р0,001 and rs=0,409, р0,01) patients with different clinical forms of NAFLD, namely at nonalcoholic hepatic steatosis and nonalcoholic steatohepatitis. Conclusions. Patients with comorbid over NAFLD in conjunction with OB and in the pathology BT observed deepening of metabolic disorders with significant changes in blood lipid-phospholipid spectrum, which significantly depend on the increase in BMI.